Arsenite oxyanions affect CeO2 nanoparticle dissolution and colloidal stability. Issue 1 (17th December 2020) - Neil, Chelsea W.; Wu, Xuanhao; Kim, Doyoon; Jung, Haesung; Zhu, Yanzhe; Ray, Jessica R.; Jun, Young-Shin
Abstract : Exposing ceria nanoparticles to high arsenite concentrations will trigger aggregation and settling, while lower concentrations promote dissolution through redox interactions. Abstract : While highly reactive cerium oxide nanoparticles (CeO2 NPs) are widely used in industry, their transport in aquatic systems is not well understood. To fill this knowledge gap, the interactions of CeO2 NPs with arsenite (As 3+ ), a toxic metalloid and potential co-present contaminant, were investigated with respect to CeO2 NP colloidal stability, dissolution, and surface redox reactions. Arsenite showed distinctive effects at different concentrations, with a high As 3+ concentration (10 −4 M) inducing 90% of CeO2 NPs to settle from solution after 8 hours, while lower As 3+ concentrations (10 −5 or 10 −6 M) led to only 20% of CeO2 NPs settling. The dissolution of NPs was most significant in the 10 −5 M As 3+ system owing to a lesser extent of aggregation, exposing more CeO2 surface for dissolution. In the three As 3+ concentration systems, >97% of aqueous arsenic remained as As 3+ over 6 hours. On the NP surface, adsorbed As III was oxidized to As V, resulting in 58–70% of the adsorbed arsenic remaining as As III . Simultaneously Ce IV was reduced to Ce III, increasing Ce III on the CeO2 NP surface from 17% (without arsenite) to 21–25% (with arsenite). Further mechanistic analyses revealed that the adsorption of arsenite was the main contributor to neutralizing the CeO2 NP surface potential, enhancing particle sedimentation. These findings suggest that the fate and transport of CeO2 NPs in our experimental systems are strongly affected by arsenite concentration and its adsorption on NPs. The results also highlight the importance of the interplay between NP aggregation, oxidation, and dissolution in predicting the behaviors of CeO2 NPs and associated toxic elements in aquatic systems.